Temporal characterization of two-octave infrared pulses by frequency resolved optical switching. (27th August 2021) - Leblanc, Adrien; Longa, Adrien; Kumar, Mayank; Laramée, Antoine; Dansereau, Charles; Ibrahim, Heide; Lassonde, Philippe; Légaré, François
Abstract: We present the temporal characterization of infrared pulses with spectra extending from 0.55 to 2.5 μ m by using the frequency resolved optical switching (FROSt) technique. The pulses are obtained by broadening femtosecond pulses at 1.75 μ m central wavelength in a two-stage hollow core fiber setup. This work demonstrates the capability of the FROSt technique to temporally characterize pulses with ultra-broadband spectra. Being free of phase-matching constraints, it enables the characterization of pulses with very low energy at the limit of the detection threshold and with arbitrary long pulse duration. This strength of the FROSt technique is illustrated by the characterization of supercontinua pulses whose spectra span over two octaves and with only 150 nJ energy that is spread temporally over almost 40 ps. The FROSt capabilities provide a versatile tool for the characterization of sub-cycle pulses and to study nonlinear processes such as supercontinuum generation.